Entrepreneurship and the Industry Life Cycle The Changing Role of Human Capital and Competences (Studies on Entrepreneurship, Structural Change and Industrial Dynamics,, 2018)
Adopting evolutionary and behavioral approaches, this volume presents the latest research advances in knowledge competencies and human capital, as well as the changing structural dynamics, highlighting their links with entrepreneurial activities. It provides a set of international, benchmark case studies on initiatives (at the national, regional or individual level) geared towards entrepreneurship development. Focusing on diverse environments, systems and life cycle stages: young, established and transition industries and markets; as well as regions, it offers a valuable guide for scholars and practitioners interested in the interaction of entrepreneurship, knowledge competencies, human resources management and innovation.